Electron Energization by High‐Amplitude Turbulent Electric Fields: A Possible Source of the Outer Radiation Belt. Issue 7 (7th July 2022) - Usanova, M. E.; Ergun, R. E.
Abstract: The turbulent energy cascade that is characteristic of bursty bulk flow (BBF) braking regions in the Earth's magnetotail has been shown to be the energy source of large‐amplitude electric fields (>50 mV/m) which can, in turn, result in local energetic electron acceleration. These pre‐energized electrons can move inward to stronger magnetic fields being further accelerated and can eventually supply an energetic tail to electron distributions in the outer radiation belt. Using wave and plasma measurements from the Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellites during four tail seasons from 2015 to 2019, we study the process of BBF magnetic and kinetic energy being transferred to electrons by turbulent electric fields from a statistical perspective. We identify turbulent BBF regions by the presence of high‐amplitude electric fields. We show that the high‐amplitude electric fields are associated with an increase in electron temperature by three times compared to quiet times and with a ten‐fold increase in temperature fluctuations. They are also associated with strong variations of energetic electron fluxes, indicative of local acceleration. We further discuss the implications of these findings and the role of this pre‐energized electron population in supplying the outer radiation belt. Plain Language Summary: Bursty bulk flows are high‐speed plasma flows, observed in Earth's nightside magnetosphere. They move toward Earth from distances 20–30 Earth radii in the magnetotail where they are generated by magnetic reconnection. Closer to Earth (6–12 Re tailward), they slow down and deflect, as their energy dissipates in a turbulent cascade. Using data from NASA THEMIS satellites, we show that high‐amplitude electric fields generated in this cascade, strongly energize electrons. If further pushed inward, these pre‐energized electrons will be accelerated by Earth's magnetic field, and can eventually supply the outer radiation belt. Key Points: Large‐amplitude electric fields can lead to ten‐fold electron temperature fluctuations and three‐fold energetic electron flux variations Temperature and flux variations rather than absolute temperature and flux values are indicative of local acceleration The accelerated electrons may serve as a seed population for the high‐energy tail of the outer radiation belt